NF-κB in Innate Neuroprotection and Age-Related Neurodegenerative Diseases - Lanzillotta, Annamaria; Porrini, Vanessa; Bellucci, Arianna; Benarese, Marina; Branca, Caterina; Parrella, Edoardo; Spano, Pier Franco; Pizzi, Marina (Frontiers in Neurology, 2015)
NF-κB factors are cardinal transcriptional regulators of inflammation and apoptosis, involved in the brain programming of systemic aging and in brain damage. The composition of NF-κB active dimers and epigenetic mechanisms modulating histone acetylation, finely condition neuronal resilience to brain insults. In stroke models the activation of NF-κB/c-Rel promotes neuroprotective effects by transcription of specific anti-apoptotic genes. Conversely, aberrant activation of NF-κB/RelA showing reduced level of total acetylation but site specific acetylation on lysine 310 triggers the expression of pro-apoptotic genes. Constitutive knockout of c-Rel shatters the resilience of substantia nigra (SN) dopaminergic (DA) neurons to aging and induces a parkinsonian like pathology in mice. c-rel-/- mice show increased level of aberrantly acetylated RelA in the basal ganglia, neuroinflammation, accumulation of alpha-synuclein and iron. Moreover, they develop motor deficits responsive to L-DOPA treatment and associated with loss of DA neurons in the SN. Here, we discuss the effect of unbalanced activation of RelA and c-Rel during aging and propose novel challenges for the development of therapeutic strategies in neurodegenerative diseases.